The Role of exclusive breastfeeding and water source in the reduction of stunting: Mediation and moderation analysis of cross-sectional data among Beninese children aged 6 months: Moderator of N@C project effect on stunting - Lokonon, Jaurès F. H.; Amoussa Hounkpatin , Waliou; Bodjrenou, Sam U.F.; Sokadjo, Morel Yves; Idohou Dossou, Nicole; Atchadé, Mintodê Nicodème; Hounkonnou, Nobert M. (Progress in Nutrition, 2022)
Background: Stunting is a public health issue in many low and middle income countries. The role played by exclusive breastfeeding practice (EBF) and water source (WS) used by the mothers in stunting reduction needs to be more clarified. Objective: To test whether EBF and WS are moderators or mediators of participation in Nutrition at Centre (N@C) project activities effect on child stunting reduction. Methods: We used cross-sectional data on 213 mothers and their 6 months’ age children from 40 villages in Southern Benin. Scores of participation in N@C activities (SPA) were estimated by counting the activities in which the mothers have participated during the  last six months. Association between prevalence of stunting (length-for-age z-score < - 2) and SPA was investigat-ed binary and multinomial logistic regression. Then, EBF and WS were included in the models to check whether they were mediators or moderators. Results: In our sample, 16% of children were stunted. High SPA of mothers was likely associated with low stunting prevalence (OR=0.92; 95% IC: 0.87-0.98). We did not have evidence to claim that neither EBF nor WS were a mediator of the effect of SPA on stunting reduction, but they were moderators. While the score of participation increased and the mothers didn’t practice EBF, the stunting prevalence increased slightly from 21.4% to 26.8%. Moreover, the score of participation increased and WS is drilling system or covered well or tap, the stunting prevalence decreased by 15.6%, 26.9%, and 45.4%, respectively. Conclusions: EBF and WS have been the moderators of SPA effect on children stunting prevalence at 6 months of age. Effective practice of EBF and the use of appropriate WS by the mothers are needed to have a large effect of participation in the nutrition community projects on the reduction of stunting.